An Explorative Note on Apraxia Tests - Gulde, Philipp; Leippold, Katharina; Armstrong, Alan; Kohl, Sarah; Grimmer, Timo; Diehl-Schmid, Janine; Hermsdörfer, Joachim (Frontiers in Neurology, 2018)
Apraxia is stated independent of primary motor disorders. However, patient groups suffering from stroke or dementia can reveal motor impairments. In this study we examined the dependence of apraxia tests of imitation and pantomime on a latent motor component using a principal component analysis. With samples sizes of eleven patients suffering from dementia of the Alzheimer’s type and 15 healthy control subjects, clear limitations concerning the validity of the results are given. Nevertheless, we could observe strong dependence of the three apraxia tests, especially the imitation of finger and hand gestures, on a latent motor component in this preliminary examination. We suggest confirmation by larger samples sizes and to control for the basic motor capacity when testing for signs of apraxia in such patient samples.